Cloud computing implementation in the public sector : factors and impact - Hasimi Sallehudin; Razli Che Razak; Mohammad Ismail; Ahmad Firdause Md Fadzil; Rogis Baker (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study is to examine the assimilation of cloud computing by measuring the organization’s assimilation of cloud as well as performance in the Malaysian public sector. This study mainly integrates the Diffusion of Innovation Theory (DOI), Technology-Organization-Environment Framework (TOE) Human-Organization-Technology (HOT-fit) model and IS Success model to understand this issue. A total of 169 agencies from the Malaysian public sector have participated in this study. Data for all the study variables have been collected through self-administered survey questionnaires and analyzed using SEM-PLS. The study has shown that the effect of the operational effectiveness of cloud implementation is at the lower level. The study also reveals that only factors of technological, organizational and human characteristics are found to have a significant effect on cloud computing implementation. The results indicate that the model provides a good understanding of the factors that influence the implementation of cloud computing as well as operational performance.